Systematic Review of Family Members in Improving the Quality of Life of People with T2DM - Gabriel Wanda Sinawang; Kusnanto Kusnanto; Ika Nur Pratiwi (Universitas Airlangga, 2020)
ABSTRACTIntroduction: Many patients with type 2 diabetes (T2DM) experience psychological issues affecting their ability to cope and manage their disease. Unfortunately, healthcare providers, including nurses, often report a lack of resources to provide sufficient support. During short and busy consultations, nurses and physicians often focus on etiology, diagnosis, pathophysiology, and treatment of the disease, while patients are more concerned with the consequences and impact on their daily life and family relations. The study aimed to find out forms of family support to improve the quality of live T2DM.Methods: Articles were framework using POCOT searching Science Direct, Scopus, Google Scholar databases, limited to the last 5 years and framework using POCOT. The articles were from 2015 to 2020 and the language used was English. The study focused on family support and Diabetic Mellitus type 2 (T2DM).Results: From 359 articles, 15 articles were included, most of the findings of the studies showed that family plays an important role in increasing self-efficacy so it contributes to blood sugar control which supports T2DM patients’ quality of life. The support that has been carried out by the family includes communication in the patient's treatment program, diet and blood sugar check, motivation in physical activity, support for medical expenses, accompanying them for controls. Patients with higher perceived diabetes-specific family and friend support had healthier behaviors.Conclusion: Family support helps improve the quality of life and reduce physical and psychological complications in people with T2DM.